Effect of Stabilizing Particle Size on the Structure and Properties of Liquid Marbles - Asaumi, Yuta; Rey, Marcel; Oyama, Keigo; Vogel, Nicolas; Hirai, Tomoyasu; Nakamura, Yoshinobu; Fujii, Syuji (Langmuir, 2020)
A liquid marble (LM) describes a liquid droplet that is wrapped by nonwetting micro- or nanoparticles and therefore obtains characteristics of a solid powder particle. Here, we investigate the effect of the stabilizing particle size on the resulting structure and properties of the LM. We synthesize a series of polystyrene particles with ultrathin coatings of heptadecafluorooctanesulfonic acid-doped polypyrrole with diameters ranging between 1 and 1000 μm by an aqueous chemical oxidative seeded polymerization of pyrrole. The methodology produced a set of hydrophobic particles with similar surface characteristics to allow the formation of LMs and to probe size effects in the LM formation and stabilization efficiency. We found that particles with a size above 20 μm adsorb as a particle monolayer to the surface of the LM, while smaller particles are adsorbed as ill-defined, multilayered aggregates. These results indicate that the balance between particle-particle interaction and gravity is an important parameter to control the surface structure of the LMs. The assembly behavior and size of the particles also correlated with the mechanical integrity of the LM against fall impact. The mechanical resistance was affected by the gap distance between the inner liquid of the LM and supporting substrate, the capillary forces acting between the particles at the LM surface, and the potential energy that depended on the particle size. Last, we demonstrate that the broadband light-absorbing properties of the polypyrrole shell also allow manipulating the evaporation rate of the inner liquid.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Polymer particles; Interfaces; Liquids; Nanoparticles; Particle size